Unveiling the Crucial Role of Type IV Secretion System and Motility of Helicobacter pylori in IL-1β Production via NLRP3 Inflammasome Activation in Neutrophils - Jang, Ah-Ra; Kang, Min-Jung; Shin, Jeong-Ih; Kwon, Soon-Wook; Park, Ji-Yeon; Ahn, Jae-Hun; Lee, Tae-Sung; Kim, Dong-Yeon; Choi, Bo-Gwon; Seo, Myoung-Won; Yang, Soo-Jin; Shin, Min-Kyoung; et al. (Frontiers in Immunology, 2020)
Helicobacter pylori is a gram-negative, microaerophilic, and spiral-shaped bacterium and causes gastrointestinal diseases in human. IL-1β is a representative cytokine produced in innate immune cells and is considered to be a key factor in the development of gastrointestinal malignancies. However, the mechanism of IL-1β production by neutrophils during H. pylori infection is still unknown. We designed this study to identify host and bacterial factors involved in regulation of H. pylori-induced IL-1β production in neutrophils. We found that H. pylori-induced IL-1β production is abolished in NLRP3-, ASC-, and caspase-1/11-deficient neutrophils, suggesting essential role for NLRP3 inflammasome in IL-1β response against H. pylori. Host TLR2, but not TLR4 and Nod2, was also required for transcription of NLRP3 and IL-1β as well as secretion of IL-1β. H. pylori lacking cagL, a key component of the type IV secretion system (T4SS), induced less IL-1β production in neutrophils than did its isogenic WT strain, whereas vacA and ureA were dispensable. Moreover, T4SS was involved in caspase-1 activation and IL-1β maturation in H. pylori-infected neutrophils. We also found that FlaA is essential for H. pylori-mediated IL-1β production in neutrophils, but not dendritic cells. TLR5 and NLRC4 were not required for H. pylori-induced IL-1β production in neutrophils. Instead, bacterial motility is essential for the production of IL-1β in response to H. pylori. In conclusion, our study shows that host TLR2 and NLRP3 inflammasome and bacterial T4SS and motility are essential factors for IL-1β production by neutrophils in response to H. pylori.